A SERVICE IMPROVING EFFORTS AT ADMINISTRATION UNIT FOR DRIVING LICENSE (SATPAS) 1459 OF POLRES SEMARANG TO ACHIEVE EXCELLENT SERVICE - Denny Hermawan Saputra (Advances in Police Science Research Journal, 2022)
Excellent service has been a central issue in public service. The same goes for SIM service at Administration Unit for Driving License (SATPAS) 1459 of Polres Semarang which has not achieved excellent service. This has motivated the researchers to investigate SIM service at SATPAS 1459 of Polres Semarang. This research sought to find out the implementation of service, the factors influencing the service, the efforts to improve service at SATPAS 1459 of Polres Semarang. This research employed mixed methods approach with embedded design type, where the quantitative approach supported the qualitative approach to ensure the data becoming more comprehensive, valid, reliable, and objective. The research objects consisted of the service, the officers, and the applicants at SATPAS 1459 of Polres Semarang. This research was conducted for two weeks, using research instruments in the form of interview guideline, observation sheet, and questionnaire. The results of interview, observation, and research data processing revealed that SATPAS 1459 of Polres Semarang lacked the quality of human resources, had inaccurate budget distribution, had not implemented the standard operating procedures, and lacked the support from infrastructure. The results also underlined the lack of knowledge and driving skills of the people of Semarang Regency and the geographical conditions of Semarang Regency. Based on the research results, it can be concluded that the service at SATPAS 1459 of Polres Semarang is not excellent service and the efforts to improve service by SATPAS 1459 of Polres Semarang have been sub-optimal due to internal factors of human resources, budget, standard operating procedures, and infrastructure, as well as external factors including the community and geographical conditions of Semarang Regency. Therefore, SATPAS 1459 of Polres Semarang needs to improve its service by using the concept of excellent service and one-stop service.